Positive electrode active material and preparation method thereof and sodium ion battery

By controlling the M'(CN)6 hole content in the positive electrode active material of sodium ion battery and optimizing the crystal frame structure, the problem of poor circulation and rate performance of sodium ion battery in the prior art is solved, and high-efficiency energy storage is achieved.

CN114335518BActive Publication Date: 2024-12-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210004959.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2017-10-30
Publication Date
2024-12-20
Estimated Expiration
2037-10-30

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode active materials have too many holes during the charging and discharging process, resulting in low cycling performance and first-time charging capacity, and poor rate performance, which cannot meet the market's demand for high-efficiency energy storage devices.

Method used

Develop a positive electrode active material with a molecular formula of AxM[M'(CN)6]y·zH2O, where A is an alkali metal or alkaline earth metal, M and M' are transition metals, and M'(CN)6 hole content control Within 0.2 mol/mol, the coprecipitation reaction rate was adjusted by sodium carboxymethylcellulose to prepare a material with an optimized crystal frame structure.

Benefits of technology

It improves the circulation performance and first-time charging capacity of sodium ion batteries, and maintains good rate performance, ensuring the stability of the battery and efficient energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114335518B_ABST
    Figure CN114335518B_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode active material and a preparation method thereof and an electrochemical energy storage device. The molecular formula of the positive electrode active material is A x M[M′(CN)6] y ·zH2O, wherein A is one or more of alkali metal ions and alkaline earth metal ions, M and M' are transition metals, 0
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the original invention patent application (with the application date of October 30, 2017, application number 201711036954.8, and invention title "Positive electrode active material, its preparation method and sodium ion battery"). Technical Field

[0002] This application relates to the field of batteries, and particularly to a positive electrode active material, its preparation method and a sodium ion battery. Background Art

[0003] In recent years, with the rapid development of electronic devices, power tools, low-power electric vehicles, etc., researching energy-efficient, resource-rich and environmentally friendly energy storage devices is a necessary condition for the sustainable development of human society.

[0004] Sodium ion batteries have been widely concerned due to their low manufacturing cost and good safety. Among them, the positive electrode active material of sodium ion batteries is the main factor affecting their performance. Therefore, to meet the huge market demand, it is urgent to develop a positive electrode active material for sodium ion batteries that has both good electrochemical performance and good kinetic performance.

[0005] In view of this, the present application is specifically proposed. Summary of the Invention

[0006] The purpose of the present application is to provide a positive electrode active material, its preparation method and a sodium ion battery. The sodium ion battery using the positive electrode active material of the present application has a relatively high initial charge capacity, and at the same time, the sodium ion battery also has good cycle performance and rate performance.

[0007] To achieve the above purpose, on the one hand of the present application, the present application provides a positive electrode active material, and the molecular formula of the positive electrode active material is A x M[M′(CN)6] y ·zH2O, where A is one or more of alkali metal ions and alkaline earth metal ions, M and M′ are transition metals, 0 < x ≤ 2, 0.8 ≤ y < 1, 0 < z ≤ 20. The content of M′(CN)6 holes in the positive electrode active material is less than or equal to 0.2 mol / mol.

[0008] On the other hand of the present application, the present application provides a preparation method of a positive electrode active material for preparing the positive electrode active material of one aspect of the present application, including the steps of: (1) dissolving a hexacyanometalate formed by metal M′ and metal A in a solvent to obtain a solution one; (2) dissolving a metal M salt in a solvent to obtain a solution two; (3) fully mixing the solution one and the solution two to obtain a mixed solution, aging to obtain a precipitate, and then washing and drying the precipitate to obtain a molecular formula of A x M[M′(CN)6]y The positive electrode active material of ·zH2O, wherein sodium carboxymethyl cellulose is added in at least one of step (1), step (2), and step (3). In another aspect of the present application, the present application provides a sodium ion battery, which includes the positive electrode active material of one aspect of the present application.

[0009] Compared with the prior art, the beneficial effects of the present application are as follows:

[0010] The positive electrode active material of the present application controls the content of holes within a certain range. On the one hand, it can improve the stability of the crystal framework structure of the positive electrode active material, thereby improving the cycling performance of the sodium ion battery. On the other hand, it can also increase the content of alkali metal or alkaline earth metal ions in the positive electrode active material, thereby improving the first charge capacity of the sodium ion battery. In addition, since the content of holes in the positive electrode active material is within a certain range, the transport channels of sodium ions in the positive electrode active material will not be blocked due to the presence of holes. Therefore, the sodium ion battery can also have better rate performance. Description of the Drawings

[0011] Figure 1 are the first charge-discharge curves of Example 1 and Comparative Example 1;

[0012] Figure 2 are the cycling performance curves of Example 1 and Comparative Example 1;

[0013] Figure 3 are the rate performance curves of Example 1 and Comparative Example 1. Detailed Embodiments

[0014] The positive electrode active material according to the present application, its preparation method, and the sodium ion battery will be described in detail below.

[0015] First, the positive electrode active material according to the first aspect of the present application will be described.

[0016] The molecular formula of the positive electrode active material according to the first aspect of the present application is A x M[M′(CN)6] y ·zH2O, wherein A is one or more of alkali metal ions and alkaline earth metal ions, M and M′ are transition metals, 0 < x ≤ 2, 0.8 ≤ y < 1, 0 < z ≤ 20. The content of M′(CN)6 holes in the positive electrode active material is less than or equal to 0.2 mol / mol, that is, the content of M′(CN)6 holes per mole of the positive electrode active material is less than or equal to 0.2 mol.

[0017] In the crystal framework structure of the positive electrode active material, the carbon ligand in the cyanide group is complexed with the transition metal M' to form a hexacoordinated octahedral structure M'(CN)6, and the uncoordinated nitrogen ligand in the M'(CN)6 octahedron is also complexed with the transition metal M to form a hexacoordinated octahedral structure M(NC)6. Therefore, the M'(CN)6 octahedron and the M(NC)6 octahedron are alternately connected to form a three-dimensional skeleton crystal structure. The alkali metal ions or alkaline earth metal ions exist in the pores of the three-dimensional skeleton structure to balance the charge. In the synthesis process of the positive electrode active material, M'(CN)6 m - anion and M n+ Once the cations are mixed, they will immediately form a precipitate. The excessively fast reaction rate can easily cause the generation of M'(CN)6 holes in the crystal framework structure of the positive electrode active material. The presence of holes will block or slow down the transmission of sodium ions in the positive electrode active material during the charge and discharge process, thereby reducing the rate performance of the positive electrode active material. Holes can also cause the crystal structure of the positive electrode active material to be unstable. Sodium ions can easily cause structural damage around the holes during the embedding and extraction process, thereby reducing the cycle performance of the positive electrode active material. The presence of holes can also reduce the content of alkali metal or alkaline earth metal ions in the crystal framework structure of the positive electrode active material, affecting the performance of the first charge capacity of the sodium ion battery. The content of M'(CN)6 holes in the positive electrode active material of the present application is low. On the one hand, sodium ions can minimize the damage to the crystal framework structure of the positive electrode active material during the embedding and extraction process, thereby improving the stability of the crystal framework structure of the positive electrode active material, thereby improving the cycle performance of the sodium ion battery. On the other hand, it can also increase the content of alkali metal or alkaline earth metal ions in the crystal framework structure of the positive electrode active material, increase the gram capacity of the positive electrode active material, and thus improve the first charge capacity of the sodium ion battery. In addition, the positive electrode active material has a low hole content, so the transmission channel of sodium ions in the positive electrode active material will not be blocked due to the presence of a large number of holes, and sodium ions have good diffusion properties in the positive electrode active material, so the sodium ion battery has better rate performance.

[0018] In the positive electrode active material according to the first aspect of the present application, preferably, in order to further improve the cycle performance of the sodium ion battery, the crystal form of the positive electrode active material may be a cubic crystal form.

[0019] In the positive electrode active material according to the first aspect of the present application, preferably, 1≤x≤2. When the content of alkali metal or alkaline earth metal A is high, it is beneficial to obtain a sodium ion battery with a higher gram capacity.

[0020] In the positive electrode active material according to the first aspect of the present application, when the water content in the positive electrode active material is high, the probability of side reactions between water and the electrolyte will increase. Therefore, more preferably, 0 <z≤5。

[0021] In the positive electrode active material according to the first aspect of the present application, preferably, in order to further improve the rate performance of the sodium ion battery, the particle size D50 of the positive electrode active material is 1.0μm to 10μm. Because the conductivity of the positive electrode active material itself is low, to achieve better rate performance, the ion and electron diffusion paths must be shortened, that is, the smaller the particle size of the positive electrode active material, the better. However, after the particle size D50 of the positive electrode active material is reduced, its specific surface area increases sharply. The excessive specific surface area increases the activity of the positive electrode active material, increases the side reactions, and is not conducive to improving the cycle performance of the sodium ion battery. On the whole, when the particle size D50 of the positive electrode active material falls within the range of 1.0μm to 10μm, the rate performance of the sodium ion battery is less affected by the ion and electron diffusion paths, that is, it is less affected by the particle size, and at the same time does not reduce its cycle performance. Further preferably, the particle size D50 of the positive electrode active material can be 1.5μm to 5μm. More preferably, the particle size D50 of the positive electrode active material may be 1.5 μm to 3 μm.

[0022] In the positive electrode active material according to the first aspect of the present application, preferably, the positive electrode active material may be in the form of secondary particles.

[0023] In the positive electrode active material according to the first aspect of the present application, preferably, A can be selected from Li + 、Na + , K + Mg 2+ , Ca 2+ Further preferably, A can be selected from Li + 、Na + , K + One or more of the .

[0024] In the positive electrode active material according to the first aspect of the present application, preferably, M can be selected from one of Mn, Fe, Co, Ni, Cu, Zn, V, and Cr. Further preferably, M can be selected from one of Mn, Fe, and Co.

[0025] In the positive electrode active material according to the first aspect of the present application, preferably, M' can be selected from one of Mn, Fe, Co, Ni, Cu, Zn, V, and Cr. Further preferably, M' can be selected from one of Mn and Fe. Even more preferably, M' is selected from Fe.

[0026] In the positive electrode active material according to the first aspect of the present application, preferably, the content of M'(CN)6 holes in the positive electrode active material is less than or equal to 0.1 mol / mol. Controlling the content of M'(CN)6 holes within this range can further improve the initial charge capacity of the sodium ion battery, and further improve the cycle performance and rate performance of the sodium ion battery.

[0027] Next, a method for preparing the positive electrode active material according to the second aspect of the present application is described.

[0028] The method for preparing the positive electrode active material according to the second aspect of the present application is used to prepare the positive electrode active material described in the first aspect of the present application, comprising the steps of:

[0029] (1) dissolving a hexacyanometallate salt formed by metal M′ and metal A in a solvent to obtain a solution 1;

[0030] (2) dissolving the metal M salt in a solvent to obtain a second solution;

[0031] (3) Solution 1 and Solution 2 are fully mixed to obtain a mixed solution, which is aged to obtain a precipitate, which is then washed and dried to obtain a precipitate having a molecular formula A. x M[M′(CN)6] y ·zH2O positive electrode active material, wherein sodium carboxymethyl cellulose is added in at least one of step (1), step (2) and step (3). The addition of sodium carboxymethyl cellulose can slow down the coprecipitation reaction rate and reduce the M′(CN)6 hole content in the positive electrode active material.

[0032] In the method for preparing the positive electrode active material according to the second aspect of the present application, preferably, sodium carboxymethyl cellulose is added in step (1), step (2) and step (3).

[0033] In the preparation method of the positive electrode active material according to the second aspect of the present application, if the amount of sodium carboxymethyl cellulose added is too little, the viscosity of the solution is too small, and it cannot slow down the rate of the coprecipitation reaction during the coprecipitation in step (3). Too fast a coprecipitation rate will make the hole content of the obtained positive electrode active material too large, which is not conducive to improving the performance of the sodium ion battery; if the amount of sodium carboxymethyl cellulose added is too much, the viscosity of the solution will be too large, making it difficult to separate the particles. Preferably, the amount of sodium carboxymethyl cellulose added in step (1) is 0.01% to 1% of the total mass of solution one. Preferably, the amount of sodium carboxymethyl cellulose added in step (2) is 0.01% to 1% of the total mass of solution two. Preferably, the amount of sodium carboxymethyl cellulose added in step (3) is 0.01% to 1% of the total mass of the mixed solution of solution one and solution two.

[0034] In the method for preparing the positive electrode active material according to the second aspect of the present application, in step (3), there is no specific limitation on the mixing method of solution 1 and solution 2, and they can be mixed according to actual needs. Specifically, solution 1 can be added dropwise to solution 2 for mixing, solution 2 can be added dropwise to solution 1 for mixing, or solution 1 and solution 2 can be added dropwise to a solvent at the same time for mixing.

[0035] In the method for preparing the positive electrode active material according to the second aspect of the present application, the type of the solvent is not specifically limited and can be selected according to actual needs. Specifically, the solvent can be selected from one or more of deionized water, ethanol, ethylene glycol, glycerol, N,N-dimethylformamide, and other polyols. The solvents in step (1), step (2), and step (3) can be the same or different. Preferably, the solvents in step (1), step (2), and step (3) are all selected from deionized water.

[0036] In the method for preparing the positive electrode active material according to the second aspect of the present application, preferably, the hexacyanometallate formed by the metal M′ and the metal A can be selected from one or more of Na4Fe(CN)6, K4Fe(CN)6, Na3Fe(CN)6, K3Fe(CN)6, K4Mn(CN)6, K3Co(CN)6, K4V(CN)6, K4Cr(CN)6, K4Ni(CN)6, Na4Mn(CN)6, Na3Co(CN)6, Na4V(CN)6, Na4Cr(CN)6, and Na4Ni(CN)6, but the present application is not limited thereto.

[0037] In the method for preparing the positive electrode active material according to the second aspect of the present application, preferably, the metal M salt can be selected from one or more of MnCl2, NiNO3, FeSO4, (CH3COO)2Zn, CoCl2, CuSO4, Fe(NO3)3, FeCl3, Fe(CH3COO)2, FeCl2, Cu(NO3)2, CuCl2, Cu(CH3COO)2, Ni(NO3)2, NiSO4, Ni(CH3COO)2, NiCl2, Mn(NO3)2, MnSO4, Mn(CH3COO)2, MnCl2, Zn(NO3)2, ZnSO4, ZnCl2, Co(NO3)2, CoSO4, and Co(CH3COO)2, but the present application is not limited thereto.

[0038] In the method for preparing the positive electrode active material according to the second aspect of the present application, in step (3), if the molar ratio of M' to M in the mixed solution is too different, it will cause waste of the excess. Preferably, in the mixed solution, the molar ratio of M' to M is 0.5 to 1.5.

[0039] In the method for preparing the positive electrode active material according to the second aspect of the present application, a reducing agent may be added in at least one of step (1), step (2), and step (3), and the reducing agent may protect the transition metal in a low valence state from being oxidized to a higher valence state. The type of the reducing agent is not specifically limited and may be selected according to actual needs. Specifically, the reducing agent may be selected from one or more of sodium thiosulfate, sodium citrate, citric acid, glucose, ascorbic acid, alcohol, aldehyde, and ketone.

[0040] In the method for preparing the positive electrode active material according to the second aspect of the present application, the amount of sodium carboxymethyl cellulose added, the concentration of M′ in step (1), and the solution mixing temperature in step (3) all have an impact on the particle size of the positive electrode active material.

[0041] In the method for preparing the cathode active material according to the second aspect of the present application, preferably, the concentration of M' in step (1) is 0.05 mol / L to 0.5 mol / L. Preferably, the concentration of M in step (2) is 0.05 mol / L to 0.5 mol / L.

[0042] In the method for preparing the positive electrode active material according to the second aspect of the present application, in step (3), the mixing temperature of solution one and solution two can be 25° C. to 100° C., and the aging time can be 1 h to 120 h.

[0043] In the method for preparing the positive electrode active material according to the second aspect of the present application, in step (3), the precipitate can be collected by suction filtration or centrifugation, and the drying time of the precipitate is no more than 60 hours.

[0044] The sodium ion battery according to the third aspect of the present application is described again.

[0045] The sodium ion battery according to the third aspect of the present application comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet comprises a positive electrode current collector and a positive electrode membrane sheet disposed on the positive electrode current collector and containing a positive electrode active material. The positive electrode active material comprises the positive electrode active material according to the first aspect of the present application.

[0046] In the sodium ion battery according to the third aspect of the present application, the negative electrode sheet may include a negative electrode current collector and a negative electrode membrane disposed on the negative electrode current collector and containing a negative electrode material, and the negative electrode material may be selected from one or more of carbon materials, alloy materials, transition metal oxides and sulfides, phosphorus-based materials, and titanate materials.

[0047] In the sodium ion battery according to the third aspect of the present application, the negative electrode sheet may also be a metallic sodium sheet or a sodium alloy sheet.

[0048] In the sodium ion battery according to the third aspect of the present application, the material of the separator is not limited and can be selected according to actual needs. Specifically, the separator can be selected from one or more of polypropylene film, polyethylene film, polyethylene / polypropylene / polyethylene composite film, cellulose non-woven film, and glass fiber film.

[0049] In the sodium ion battery according to the third aspect of the present application, preferably, an organic electrolyte system is used.

[0050] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0051] Example 1

[0052] (1) Preparation of positive electrode

[0053] 4.84 g Na4Fe(CN)6·10H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 1.97 g MnCl2·4H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at room temperature, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution with stirring, and the solution was aged for 6 h after the addition was completed. The precipitate obtained after aging was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24 h to obtain a positive electrode active material sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.978 Mn[Fe(CN)6] 0.994 ·1.961H2O, the particle size test results show that the D50 of this sample is 1.5μm.

[0054] The above-mentioned positive electrode active material was mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1, and the solvent N-methylpyrrolidone was added. The mixture was stirred under the action of a vacuum mixer until the system became uniform to obtain a positive electrode slurry, which was then coated on a positive electrode current collector aluminum foil with a thickness of 15 μm. After drying at 80°C, it was punched into a positive electrode sheet with a diameter of 14 mm.

[0055] (2) Preparation of negative electrode sheet

[0056] The negative electrode sheet is directly selected from the metallic sodium sheet.

[0057] (3) Preparation of electrolyte

[0058] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC) and propylene carbonate (PC) were mixed in a volume ratio of 1:1, and then fully dried sodium salt NaClO4 was dissolved in a mixed organic solvent to obtain an electrolyte, in which the concentration of NaClO4 was 1 mol / L.

[0059] (4) Preparation of isolation membrane

[0060] A glass fiber membrane (produced by Whatman) was used as an isolation membrane.

[0061] (5) Preparation of button batteries

[0062] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and placed in a packaging shell, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the prepared electrolyte is injected to assemble a CR2032 button battery.

[0063] Example 2

[0064] The preparation process of the button cell is the same as that of Example 1, except that:

[0065] (1) Preparation of positive electrode

[0066] The content of sodium carboxymethyl cellulose in the Na4Fe(CN)6 solution is 0.2%;

[0067] The content of sodium carboxymethyl cellulose in the MnCl2 solution is 0.2%;

[0068] The results of ICP and TG tests showed that the molecular formula of the sample was Na 1.780 Mn[Fe(CN)6] 0.943 2.062H2O;

[0069] The particle size test results show that the D50 of the sample is 1.4μm.

[0070] Example 3

[0071] The preparation process of the button cell is the same as that of Example 1, except that:

[0072] (1) Preparation of positive electrode

[0073] The content of sodium carboxymethyl cellulose in the Na4Fe(CN)6 solution is 0.05%;

[0074] The content of sodium carboxymethyl cellulose in the MnCl2 solution is 0.05%;

[0075] The results of ICP and TG tests showed that the molecular formula of the sample was Na 1.585 Mn[Fe(CN)6]0.896 3.002H2O;

[0076] The particle size test results show that the D50 of the sample is 1.2μm.

[0077] Example 4

[0078] The preparation process of the button cell is the same as that of Example 1, except that:

[0079] (1) Preparation of positive electrode

[0080] The content of sodium carboxymethyl cellulose in the Na4Fe(CN)6 solution is 0.02%;

[0081] The content of sodium carboxymethyl cellulose in the MnCl2 solution is 0.02%;

[0082] The results of ICP and TG tests showed that the molecular formula of the sample was Na 1.390 Mn[Fe(CN)6] 0.848 3.811H2O;

[0083] The particle size test results show that the D50 of the sample is 1.0 μm.

[0084] Example 5

[0085] The preparation process of the button cell is the same as that of Example 1, except that:

[0086] (1) Preparation of positive electrode

[0087] The content of sodium carboxymethyl cellulose in the Na4Fe(CN)6 solution is 0.01%;

[0088] The content of sodium carboxymethyl cellulose in the MnCl2 solution is 0.01%;

[0089] The results of ICP and TG tests showed that the molecular formula of the sample was Na 1.189 Mn[Fe(CN)6] 0.800 3.833H2O;

[0090] The particle size test results show that the D50 of the sample is 1.0 μm.

[0091] Example 6

[0092] The preparation process of the button cell is the same as that of Example 1, except that:

[0093] (1) Preparation of positive electrode

[0094] 4.22g K4Fe(CN)6·3H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.1mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a K4Fe(CN)6 solution; 1.97g MnCl2·4H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.1mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at room temperature, the MnCl2 solution was slowly added dropwise to the K4Fe(CN)6 solution with stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was K 1.596 Mn[Fe(CN)6] 0.898 ·3.155H2O, the particle size test results show that the D50 of this sample is 1.4μm.

[0095] Example 7

[0096] The preparation process of the button cell is the same as that of Example 1, except that:

[0097] (1) Preparation of positive electrode

[0098] 4.84 g Na4Fe(CN)6·10H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 1.99 g FeCl2·4H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a FeCl2 solution; at room temperature, the FeCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution with stirring, and the solution was aged for 6 h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24 h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.701 Fe[Fe(CN)6] 0.920 ·2.597H2O, the particle size test results show that the D50 of this sample is 1.1μm.

[0099] Example 8

[0100] The preparation process of the button cell is the same as that of Example 1, except that:

[0101] (1) Preparation of positive electrode

[0102] 4.84 g Na4Fe(CN)6·10H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 1.97 g MnCl2·4H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at room temperature, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution with stirring, and the solution was aged for 6 h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24 h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.989 Mn[Fe(CN)6] 0.997 ·2.185H2O, the particle size test results show that the D50 of this sample is 3.0μm.

[0103] Example 9

[0104] The preparation process of the button cell is the same as that of Example 1, except that:

[0105] (1) Preparation of positive electrode

[0106] 4.84 g Na4Fe(CN)6·10H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.7% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 1.97 g MnCl2·4H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.1 mol / L, and then 0.7% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at room temperature, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution with stirring, and the solution was aged for 6 h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24 h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.980 Mn[Fe(CN)6] 0.995 ·2.195H2O, the particle size test results show that the D50 of this sample is 2.1μm.

[0107] Example 10

[0108] The preparation process of the button cell is the same as that of Example 1, except that:

[0109] (1) Preparation of positive electrode

[0110] 2.42g Na4Fe(CN)6·10H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.05mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 0.99g MnCl2·4H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.05mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at 30°C, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.877 Mn[Fe(CN)6] 0.969 ·2.098H2O, the particle size test results show that the D50 of this sample is 5.0μm.

[0111] Embodiment 11

[0112] The preparation process of the button cell is the same as that of Example 1, except that:

[0113] (1) Preparation of positive electrode

[0114] 1.45g Na4Fe(CN)6·10H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.03mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 0.59g MnCl2·4H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.03mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at 50°C, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.788 Mn[Fe(CN)6] 0.947 ·2.105H2O, the particle size test results show that the D50 of this sample is 8.0μm.

[0115] Example 12

[0116] The preparation process of the button cell is the same as that of Example 1, except that:

[0117] (1) Preparation of positive electrode

[0118] 0.97g Na4Fe(CN)6·10H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.02mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 0.40g MnCl2·4H2O was dissolved in 100ml deionized water to prepare a solution with a concentration of 0.02mol / L, and then 1% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at 80°C, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.752 Mn[Fe(CN)6] 0.938 ·2.185H2O, the particle size test results show that the D50 of this sample is 10.0μm.

[0119] Comparative Example 1

[0120] The preparation process of the button cell is the same as that of Example 1, except that:

[0121] (1) Preparation of positive electrode

[0122] 4.84g Na4Fe(CN)6·10H2O was dissolved in 100ml deionized water to prepare a Na4Fe(CN)6 solution with a concentration of 0.1mol / L; 1.97g MnCl2·4H2O was dissolved in 100ml deionized water to prepare a MnCl2 solution with a concentration of 0.1mol / L; at room temperature, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, then washed, and finally dried in a drying oven at 100℃ for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.138 Mn[Fe(CN)6] 0.784 ·5.834H2O, the particle size test results show that the D50 of this sample is 1.5μm.

[0123] Comparative Example 2

[0124] The preparation process of the button cell is the same as that of Example 1, except that:

[0125] (1) Preparation of positive electrode

[0126] 14.52g Na4Fe(CN)6·10H2O was dissolved in 100ml deionized water, and then 0.03% sodium carboxymethyl cellulose (CMC-Na) was added to prepare a Na4Fe(CN)6 solution with a concentration of 0.3mol / L; 5.91g MnCl2·4H2O was dissolved in 100ml deionized water, and then 0.03% sodium carboxymethyl cellulose (CMC-Na) was added to prepare a MnCl2 solution with a concentration of 0.3mol / L; at 30°C, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6h after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24h to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.6811 Mn[Fe(CN)6] 0.92 ·2.877H2O, the particle size test results show that the D50 of this sample is 0.6μm.

[0127] Comparative Example 3

[0128] The preparation process of the button cell is the same as that of Example 1, except that:

[0129] (1) Preparation of positive electrode

[0130] 0.484 g Na4Fe(CN)6·10H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.01 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a Na4Fe(CN)6 solution; 0.197 g MnCl2·4H2O was dissolved in 100 ml deionized water to prepare a solution with a concentration of 0.01 mol / L, and then 0.5% sodium carboxymethyl cellulose (CMC-Na) was added and stirred to obtain a MnCl2 solution; at 90°C, the MnCl2 solution was slowly added dropwise to the Na4Fe(CN)6 solution under stirring, and the solution was aged for 6 hours after the addition was completed. After aging, the precipitate was collected by centrifugation, washed, and finally dried in a drying oven at 100°C for 24 hours to obtain a sample. The ICP and TG test results showed that the molecular formula of the sample was Na 1.742 Mn[Fe(CN)6] 0.935 ·2.412H2O, the particle size test results show that the D50 of this sample is 12μm.

[0131] Next, the button battery was tested.

[0132] (1) ICP test of positive electrode active materials

[0133] The chemical composition of the synthesized positive electrode active material was analyzed by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The content of each metal element was tested, and the obtained results were converted into the molar content of the corresponding metal element, and the molar content of holes per mole of material was calculated according to the formula. x M[M′(CN)6] y For ·zH2O, the molar content of M and M' in each mole of material can be calculated by ICP, and the molar content of M'(CN)6 holes in each mole of positive electrode active material = 1-molar content of M' / molar content of M.

[0134] (2) First charge capacity test

[0135] The first charging capacity test was carried out on the Land battery tester, wherein the current during the test of Examples 1-5, Examples 7-12, and Comparative Examples 1-3 was 0.1C (1C=170mAh / g), and the cut-off voltage for charge and discharge was 2.0V~4.0V; the current during the test of Example 6 was 0.1C (1C=155mAh / g), and the cut-off voltage for charge and discharge was 2.0V~4.0V.

[0136] (3) Cyclic performance test

[0137] 50 cycles of charge and discharge tests were performed on the Land battery tester, wherein the current during the tests of Examples 1-5, Examples 7-12, and Comparative Examples 1-3 was 0.1C (1C=170mAh / g), and the cut-off voltage for charge and discharge was 2.0V~4.0V; the current during the test of Example 6 was 0.1C (1C=155mAh / g), and the cut-off voltage for charge and discharge was 2.0V~4.0V.

[0138] (4) Rate performance test

[0139] The rate performance test was conducted on a Land battery tester. The current sizes used in the tests of Examples 1-5, Examples 7-12, and Comparative Examples 1-3 were 0.1C, 0.2C, 0.5C, and 1C, respectively, where 1C = 170 mAh / g, and the cut-off voltage for charge and discharge was 2.0V to 4.0V; the current sizes used in the test of Example 6 were 0.1C, 0.2C, 0.5C, and 1C, respectively, where 1C = 155 mAh / g, and the cut-off voltage for charge and discharge was 2.0V to 4.0V.

[0140] Table 1 Performance test results of Examples 1-12 and Comparative Examples 1-3

[0141]

[0142]

[0143] In Examples 1-12, when the molar content of holes is relatively high, the initial charge capacity of the battery is relatively low, and the capacity retention rate after 50 cycles is also relatively low. This is mainly because, on the one hand, when the molar content of holes in the positive electrode active material increases, the number of sites in the positive electrode active material that can store sodium ions decreases, resulting in a relatively low initial charge capacity of the battery; on the other hand, when the molar content of holes in the positive electrode active material increases, as sodium ions are embedded and extracted during the charge and discharge process, the structure near the holes becomes unstable, and even structural collapse may occur. Therefore, when the molar content of holes is high, the cycle stability of the battery is poor. In Comparative Example 1, the molar content of holes is too high, and the initial charge capacity and cycle performance of the battery are very poor, which can hardly meet normal usage requirements. Combined with Figure 1 and Figure 2 The first charge capacity of the battery of Example 1 reaches 168.1 mAh / g, and the capacity retention rate after 50 cycles reaches 94%, while the first charge capacity of the battery of Comparative Example 1 is only 96.1 mAh / g, and the capacity retention rate after 50 cycles is only 49%.

[0144] At the same time, it can also be analyzed in Examples 1-12 that when the molar content of holes is relatively high, the capacity retention rate of the battery at different charge and discharge rates is relatively low. This is mainly because, after the molar content of holes in the positive electrode active material increases, the holes are occupied by a large amount of coordinated water, and some sodium ions cannot diffuse through the holes to other locations of the positive electrode active material. The diffusion channels of sodium ions in the positive electrode active material are "blocked", which affects the transmission of sodium ions and leads to relatively poor rate performance. And when the current is small, sodium ions can bypass the holes to diffuse, but under high current, the sodium ions do not have time to bypass the holes and the charge and discharge process is completed, so the higher the charge and discharge rate of the battery, the worse the battery rate performance. In Comparative Examples 1-3, the molar content of holes is too high, and the rate performance of the battery is very poor. Combined with Figure 3 The capacity retention rates of the batteries of Example 1 and Comparative Example 1 are relatively similar at charge and discharge currents of 0.1C and 0.2C, but the difference in capacity retention rates becomes larger and larger as the charge and discharge current increases. When the charge and discharge current is 1C, the capacity retention rate of the battery of Example 1 is still 86.2%, while the capacity retention rate of the battery of Comparative Example 1 is only 48.0%.

[0145] By comparing the rate performance of Examples 1-12 and Comparative Examples 2-3, it is known that when the particle size of the positive electrode active material falls between the preferred range (1 μm to 10 μm), the difference in battery rate performance is mainly affected by the hole content, and when the particle size of the positive electrode active material is outside the preferred range, the effect of particle size on battery rate performance gradually becomes prominent. The hole content of Example 2 and Comparative Example 3 is almost the same, but the particle size is quite different. The rate performance of Comparative Example 3 with a particle size of 12 μm is very poor, and the capacity retention rate is only 21.1% during 1C charge and discharge. In contrast, Example 2 still has a capacity retention rate of 80.4%, and Example 2 shows better rate performance. The hole content of Example 7 is not much different from that of Comparative Example 2, but the particle size of Comparative Example 2 is smaller, only 0.6 μm. The smaller particle size causes the specific surface area of ​​the positive electrode active material to be too large, thereby increasing the probability of side reactions, so the battery cycle performance is poor.

[0146] In Examples 6-7, although the specific types of the positive electrode active materials are different, the batteries still have better cycle performance and rate performance, and have higher first charge capacity, compared with Comparative Examples 1-3.

[0147] In summary, the positive electrode active material provided in the present application controls the molar content of holes within a certain range, which can significantly improve the initial charging capacity, cycle performance and rate performance of the battery.

[0148] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A method for preparing a positive electrode active material, characterized in that: Includes steps: (1) dissolving a hexacyanometallate salt formed by metal M′ and metal A in a solvent to obtain a solution 1; (2) dissolving the metal M salt in a solvent to obtain a solution 2; (3) Mix Solution 1 and Solution 2充分混合,获得混合溶液,陈化后得到沉淀物,之后沉淀物经洗涤、干燥,获得分子式为A x M[M′(CN)6] y ·zH2O的 positive electrode active material; wherein, A is an alkali metal ion Na + , M is selected from transition metal Mn, M′ is selected from transition metal Fe, 1 < x ≤ 2, 0.995 ≤ y < 1, 0 < z ≤ 2.195; and the content of M′(CN)6 holes in the positive electrode active material is less than or equal to 0.005 mol / mol; the particle size D50 of the positive electrode active material is 2.1 μm to 3.0 μm; It should be noted that there is an unclear expression "充分混合" in the original Chinese. You may need to check and clarify the accurate description for a more precise translation. Wherein, after the hexacyanometallic salt is dissolved in a solvent in step (1), sodium carboxymethyl cellulose is added to the solvent to obtain the solution 1; the amount of sodium carboxymethyl cellulose added is 0.01% to 1% of the total mass of the solution 1; And / or, after dissolving the metal M salt in a solvent in step (2), sodium carboxymethyl cellulose is added to the solvent to obtain the second solution; the amount of sodium carboxymethyl cellulose added is 0.01% to 1% of the total mass of the second solution.

2. A positive electrode active material, characterized in that: The positive electrode active material is prepared by the method for preparing the positive electrode active material according to claim 1.

3. The positive electrode active material according to claim 2, characterized in that The positive electrode active material has a cubic crystal form.

4. A sodium ion battery comprising: A positive electrode sheet, comprising a positive electrode current collector and a positive electrode membrane sheet disposed on the positive electrode current collector and containing a positive electrode active material; Negative electrode; Isolation film; as well as Electrolyte; It is characterized in that the positive electrode active material includes the positive electrode active material prepared by the method for preparing the positive electrode active material according to claim 1 or the positive electrode active material according to any one of claims 2-3.